Tumor Necrosis Factor Alpha, Obesity and Polycystic Ovarian Syndrome (Medical Forum Monthly, 2024)
Objective: To determine the level of tumor necrosis factor alpha in polycystic ovarian syndrome and to find out correlation of TNF- α with BMI in obese and non-obese females.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the outpatient Department of Lady Aitcheson Hospital Lahore 1st July 2016 to 31st December 2016.Materials and Methods: Eighty female patients diagnosed with PCOS were selected. Their height in meters (m) and weight in kg was determined and they were divided into cases with BMI> 25kg/m2 and controls with BMI<25kg/m2. 5ml of blood was taken from antecubital vein to measure serum TNF-alpha by ELISA kit.Results: The mean age of cases and controls was 25.42±4.16 years and 22.98±3.35 years, with significantly lower mean age in controls, p-value < 0.001. The mean BMI was 27.59±5.72 kg/m2 in cases and 22.74±4.44 kg/m2 in controls with significantly higher mean BMI in cases, p-value < 0.001. Mean TNF-α was statistically higher in cases (66.14±122.37 pg/ml) when compared to controls (19.98±37.10 pg/ml), p-value < 0.05.Conclusion: Serum TNF-alpha was increased in females with PCOS in both cases and controls but levels are significantly higher in cases. No significant correlation was found between TNF-alpha and BMI in either cases and controls. TNF- α level can be used as a molecular marker of disease.